Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/cbm.1881
|View full text |Cite
|
Sign up to set email alerts
|

Procedural justice and prisoners' mental health problems: A longitudinal study

Abstract: These findings suggest a causal relationship between procedural justice and psychological well-being. Fair and respectful treatment of prisoners is a predictor not only of prison order and prisoners' compliance but also of prisoners' psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 29 publications
8
46
1
2
Order By: Relevance
“…Available research suggests prison climates perceived to be of higher quality can be associated with better outcomes than lower quality climates. Beijersbergen et al (2014) found procedurally just (fair and respectful) treatment positively predicted prisoner psychological wellbeing. Gadon et al (2006) linked supportive prison management with reduced numbers of physical assaults and lower rates of inmate homicide.…”
Section: Prison Climate Qualitymentioning
confidence: 86%
“…Available research suggests prison climates perceived to be of higher quality can be associated with better outcomes than lower quality climates. Beijersbergen et al (2014) found procedurally just (fair and respectful) treatment positively predicted prisoner psychological wellbeing. Gadon et al (2006) linked supportive prison management with reduced numbers of physical assaults and lower rates of inmate homicide.…”
Section: Prison Climate Qualitymentioning
confidence: 86%
“…El afrontamiento de tipo evitativo, que fue el identificado en los condenados, tiende a considerarse como una forma desadaptativa o improductiva, al menos fuera del medio penitenciario (Arce et al, 2014). Aunque en algunos trabajos se sugiere que en el contexto de prisión las estrategias evitativas podrían ser efectivas (Beijersbergen et al, 2014;Van Harreveld et al, 2007), recurrir en menor medida a la estrategia de análisis lógico no parece reportar ningún aspecto positivo. Se trata de una estrategia útil dentro y fuera del medio penitenciario.…”
Section: Contraste De La Muestra De Condenados Por Homicidio Con La Munclassified
“…Por ejemplo, si bien fuera del recinto carcelario se considera que las estrategias centradas en el problema resultan más adaptativas, algunos resultados evidencian que, en el contexto penitenciario y ante determinadas demandas ambientales, las estrategias de tipo pasivo-evitativo se erigen como efectivas y con impacto positivo sobre la salud mental (Van Harreveld, Van der Pligt, Claassen y Van Dijk, 2007). Una posible causa de este resultado parece radicar en que dentro del contexto de prisión se restringen determinadas conductas, lo que aconseja adaptar las estrategias de afrontamiento a la situación específica (Beijersbergen, Dirkzwager, Eichelsheim, Van der Laan y Nieuwbeerta, 2014).…”
Section: Introductionunclassified
“…Cross-sectional and experimental studies have demonstrated that individuals experiencing unfair relative to fair procedures (e.g., not being allowed to voice their opinions in group decision) report lower levels of selfesteem (Koper et al 1993;De Cremer et al 2005). Additionally, procedural fairness influences self-reported well-being (Schmitt & Dörfel 1999) and mental health of individuals (Beijersbergen et al 2014). …”
Section: Procedural Fairness As a Diagnostic Toolmentioning
confidence: 99%